Photoelectrochemical Stability and Alteration Products of n-Type Single-Crystal ZnO Photoanodes. (13th February 2011) - Paulauskas, I. E.; Jellison, G. E.; Boatner, L. A.; Brown, G. M.
Abstract : The photoelectrochemical stability and surface-alteration characteristics of doped and undoped n-type ZnO single-crystal photoanode electrodes were investigated. The single-crystal ZnO photoanode properties were analyzed using current-voltage measurements plus spectral and time-dependent quantum-yield methods. These measurements revealed a distinct anodic peak and an accompanying cathodic surface degradation process at negative potentials. The features of this peak depended on time and the NaOH concentration in the electrolyte, but were independent of the presence of electrode illumination. Current measurements performed at the peak indicate that charging and discharging effects are apparently taking place at the semiconductor/electrolyte interface. This result is consistent with the significant reactive degradation that takes place on the ZnO single crystal photoanode surface and that ultimately leads to the reduction of the ZnO surface to Zn metal. The resulting Zn-metal reaction products create unusual, dendrite-like, surface alteration structural features that were analyzed using x-ray diffraction, energy-dispersive analysis, and scanning electron microscopy. ZnO doping methods were found to be effective in increasing the n-type character of the crystals. Higher doping levels result in smaller depletion widths and lower quantum yields, since the minority carrier diffusion lengths are very short in these materials.